Grading System for Schools - Singh, Avtar (JOURNAL OF INDIAN EDUCATION, 2010)
Reforms in the examination system are often recommended, sometimes discussed and rarely implemented. Introduction of Grading System in Assessment is one of such reforms which have undergone a painful journey. Very few state education boards have attempted to declare results in terms of grades in some or other form. CBSE is on the threshold of replacing marks by grades for Class IX in 2010 and Class X board examination in 2011. Therefore, a detailed picture about grades, usefulness of different types of grading scales and their implications are presented in this paper for better understanding and acceptability by this reform.